2021
DOI: 10.1590/1516-4446-2020-1169
|View full text |Cite
|
Sign up to set email alerts
|

Appraising the effectiveness of electrical and magnetic brain stimulation techniques in acute major depressive episodes: an umbrella review of meta-analyses of randomized controlled trials

Abstract: Electrical and magnetic brain stimulation techniques present distinct mechanisms and efficacy in the acute treatment of depression. This was an umbrella review of meta-analyses of randomized controlled trials of brain stimulation techniques for managing acute major depressive episodes. A systematic review was performed in the PubMed/MEDLINE databases from inception until March 2020. We included the English language meta-analysis with the most randomized controlled trials on the effects of any brain stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…The research evidence supporting its efficacy has been summarised in numerous meta-analyses and subsequently in umbrella reviews and network meta-analyses. Individual meta-analyses and the recent umbrella review (Razza et al, 2020) have clearly confirmed that rTMS is an effective treatment for patients with MDD and is safe and well tolerated. Network meta-analysis have confirmed that there are several forms of rTMS that are effective and importantly that it has comparable, if not superior, efficacy when compared to other interventions for patients with TRD.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The research evidence supporting its efficacy has been summarised in numerous meta-analyses and subsequently in umbrella reviews and network meta-analyses. Individual meta-analyses and the recent umbrella review (Razza et al, 2020) have clearly confirmed that rTMS is an effective treatment for patients with MDD and is safe and well tolerated. Network meta-analysis have confirmed that there are several forms of rTMS that are effective and importantly that it has comparable, if not superior, efficacy when compared to other interventions for patients with TRD.…”
Section: Discussionmentioning
confidence: 94%
“…A recent umbrella review has also evaluated the evidence for the efficacy of rTMS using the rigorous GRADE approach to assess the quality of evidence across existing meta-analysis (Razza et al, 2020). ‘High-quality evidence’ was found to support the efficacy of high-frequency left-sided rTMS and sequential bilateral rTMS.…”
Section: The Evidence For the Effectiveness Of Rtms In Depressionmentioning
confidence: 99%
“…As has been presented recently in this journal (Fitzgerald et al, 2021a) and described extensively elsewhere (e.g. Brunoni et al, 2017; Papadimitropoulou et al, 2017; Razza et al, 2020), these statements are inaccurate (see Table 1). In fact, there already exists a substantive evidence base supporting the use of rTMS in the treatment of depression that extends from multisite clinical trials to multiple meta-analyses, network meta-analyses, umbrella reviews and large-scale real-world treatment outcome data (Fitzgerald et al, 2021a).…”
mentioning
confidence: 89%
“…This is why a recent publication by Razza et al 1 is of importance. Clearly, many people in the psychiatric community have been unconvinced by the barrage of clinical trials, larger multisite trials, and numerous meta-analyses (e.g., Berlim et al 2 and Mutz et al 3 ) and comparative analyses showing the relative efficacy of rTMS compared to other treatment options for depression.…”
mentioning
confidence: 98%